Oxidative stress index may play a key role in patients with pemphigus vulgaris. (10th February 2012) - Yesilova, Y.; Ucmak, D.; Selek, S.; Dertlioğlu, S.B.; Sula, B.; Bozkus, F.; Turan, E.
Abstract Background Increased reactive oxygen species (ROS) and lipid peroxidation are seen in many dermatologic disorders, including atopic dermatitis, psoriasis, vitiligo, acne vulgaris, pemphigus vulgaris (PV), lichen planus and alopecia areata. In PV, the increased production of ROS from activated neutrophils reduces the concentrations of antioxidant vitamins and enzymes. Objective The present study aims to determine the oxidative stress index (OSI) by studying serum total oxidant capacity (TOC), lipid hydroperoxide (LOOH) and total antioxidant capacity (TAC) in PV patients. Methods The study included 27 PV patients and a control group consisting of 24 healthy volunteers. Serum TOC, LOOH and TAC levels were examined and OSI was measured in the PV patients and the control group. Results TOC (P = 0.001) and LOOH (P = 0.001) levels as well as OSI (P = 0.001) were found higher in the PV patients, relative to the control group. Serum TAS (P = 0.221) did not differ between groups. Serum TOC, LOOH and TAC levels and OSI in PV patients with mucosal involvement were not different than those in mucocutaneous PV patients. Conclusion Serum TOC and LOOH levels and OSI were higher in the PV patients, in comparison with the control group. Serum TAC level was not different.